2003
DOI: 10.1097/01.asn.0000067412.18899.9b
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized LDL and its Compound Lysophosphatidylcholine Potentiate AngII-Induced Vasoconstriction by Stimulation of RhoA

Abstract: RhoA stimulates vascular tone by increasing smooth muscle Ca(2+) sensitivity, e.g., in atherosclerosis. This study was an investigation of the influence of oxidized LDL (OxLDL), which accumulates in atherosclerotic plaques, on vascular tone induced by angiotensin II (AngII), with particular emphasis on the RhoA pathway. OxLDL had no influence on unstimulated vascular tone of isolated rabbit aorta, but it potentiated contractile responses induced by AngII. The Ca(2+)-antagonist felodipin partially prevented pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 38 publications
1
25
0
2
Order By: Relevance
“…Downstream RhoA, Rho-kinases have been also shown to be upregulated at inflammatory arteriosclerotic lesions in both a porcine model of coronary artery spasm (211) and arteriosclerotic human arteries (212). In agreement with this observation, in vitro studies have shown that oxidized LDL and its compound LPA activate RhoA in vascular smooth muscle and endothelial cells, suggesting that hyperlipidemia could contribute to the increased RhoA activity in the wall of atherosclerotic arteries (130,470). A causal role of RhoA/Rho-kinase signaling in the progression of plaques was first provided by pharmacological analyses that showed that in vivo chronic treatment with Rhokinase inhibitors strongly reduced atherosclerotic lesions and spasms in pig (320) and in ldlr Ϫ/Ϫ mice (289).…”
Section: Rho Proteinsmentioning
confidence: 57%
“…Downstream RhoA, Rho-kinases have been also shown to be upregulated at inflammatory arteriosclerotic lesions in both a porcine model of coronary artery spasm (211) and arteriosclerotic human arteries (212). In agreement with this observation, in vitro studies have shown that oxidized LDL and its compound LPA activate RhoA in vascular smooth muscle and endothelial cells, suggesting that hyperlipidemia could contribute to the increased RhoA activity in the wall of atherosclerotic arteries (130,470). A causal role of RhoA/Rho-kinase signaling in the progression of plaques was first provided by pharmacological analyses that showed that in vivo chronic treatment with Rhokinase inhibitors strongly reduced atherosclerotic lesions and spasms in pig (320) and in ldlr Ϫ/Ϫ mice (289).…”
Section: Rho Proteinsmentioning
confidence: 57%
“…Data also showed that the activities of RhoA and Rac1 were enhanced in atherosclerotic lesions with cellular infiltration at 7 months compared with early atherosclerotic lesions at 3 months. These findings suggest that the potency of the increased pool of unprocessed RhoA and Rac1 may play a role in the pathogenesis of Although it has been reported that oxidized LDL and LPC activate RhoA in isolated rabbit aortas, which is involved in angiotensin -induced vasoconstriction, other studies have shown that spontaneously hypertensive rats have higher protein levels of RhoA in tail arteries than control rats 21,22) . Moreover, vascular Rac1 has been shown to increase in atherogenic animal models in vivo 12,23,24) .…”
Section: Discussionmentioning
confidence: 95%
“…OxLDL potentiates Ang II-mediated vasoconstriction. 27 Treatment with AT 1 receptor blocker attenuated aortic intimal proliferation and markedly decreased the enhanced LOX-1 expression in the aorta of hypercholesterolemic animals. 28 In this clinical study, no significant synergy between both therapies could be shown.…”
Section: Discussionmentioning
confidence: 95%